2017
DOI: 10.1093/geront/gnx180
|View full text |Cite
|
Sign up to set email alerts
|

“She Had a Smile on Her Face as Wide as the Great Australian Bite”: A Qualitative Examination of Family Perceptions of a Therapeutic Robot and a Plush Toy

Abstract: Family members were keen for their older relative with dementia to use a social robot that moved and engaged with them, and Plush Toys that were static and unresponsive were perceived as being unimportant in improving quality of life. However, the current cost of Paro was identified by family members as a major limitation to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 22 publications
(23 reference statements)
2
76
0
Order By: Relevance
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
“…A low risk of bias for random sequence generation was observed for the majority of the trials, suggesting that selection bias across the studies was low. Most studies performed poorly in terms of the blinding of participants and personnel, with only one study at a low risk of bias for this criterion (Moyle et al, ). The majority of the studies performed power calculations, and 4 of the trials clearly accounted for all of their participants in the reporting of the studies (Joranson et al, ; Moyle et al, , ; Robinson et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations